Non-cognitive child outcomes and universal high quality child care - Nabanita Datta Gupta; Marianne Simonsen (Institute for the Study of Labor (IZA), 2007)
Exploiting a rich panel data child survey merged with administrative records along with a pseudo-experiment generating variation in the take-up of pre-school across municipalities, we provide evidence of the effects on non-cognitive child outcomes of participating in large scale publicly provided universal pre-school programs and family day care vis-à-vis home care. We find that, compared to home care, being enrolled in pre-school at age three does not lead to significant differences in child outcomes at age seven no matter the gender or mother's level of education. Family day care, on the other hand, seems to significantly deteriorate outcomes for boys whose mothers have a lower level of education. Finally, increasing hours in family day care from 30-40 hours per week to 40-50 hours per week and hours in pre-school from 20-30 hours per week to 30-40 hours per week leads to significantly poorer child outcomes.
Keywords: J13; 300; Non-cognitive outcomes; publicly provided universal child care; pseudo-experiment; Kinderbetreuung; Allgemeinbildende Schule; Kognition; Persönlichkeitspsychologie; Qualifikation; Mütter; Bildungsniveau; Dänemark